MEASUREMENT OF CHARGED AND NEUTRAL-CURRENT E(-)P DEEP-INELASTIC SCATTERING CROSS-SECTIONS AT HIGH Q(2) - Derrick, M; Krakauer, D; Magill, S; Mikunas, D; Musgrave, B; Repond, J; Stanek, R; Talaga, R; Zhang, H; Ayad, R; Bari, G; Basile, M; et al. (1995)
Deep inelastic e-p scattering has been studied in both the charged current (CC) and neutral current (NC) reactions at momentum transfers squared Q2 above 400 GeV2 using the ZEUS detector at the HERA ep collider. The CC and NC total cross sections, the NC to CC cross section ratio, and the differential cross sections d/dQ2 are presented. From the Q2 dependence of the CC cross section, the mass term in the CC propagator is determined to be MW=76 16 13 GeV. © 1995 The American Physical Society.